Growth Hormone Effects on Bone Loss-Induced by Mild Traumatic Brain Injury and/or Hind Limb Unloading - Kesavan, Chandrasekhar (Sci Rep, 2019)
Growth hormone (GH) deficiency and loss of physical activity are common features in traumatic brain injury (TBI) patients that may contribute to bone loss. Therefore, we tested the hypothesis that GH treatment will rescue the hind limb unloading (UL)-induced skeletal deficit in TBI mice. Mild TBI was induced once per day for four consecutive days. UL (right hind limb) and treatment (3 mg/day GH or vehicle) began two weeks after the first TBI episode and lasted for four weeks. GH treatment increased femur BMD and lean body mass but decreased the % fat measured by DXA in the Control group. Micro-CT analysis revealed that the TBI, UL and TBI-UL groups showed reduced tibia trabecular (Tb) bone mass by 15%, 70%, and 75%, respectively compared to Control mice and that GH treatment significantly increased Tb. bone mass in all four groups. Vertebra also showed reduced Tb. bone mass in TBI, UL and TBI-UL groups. GH treatment increased vertebral Tb. bone mass in Control and UL groups but not in the TBI or TBI-UL group. GH treatment increased serum IGF-I levels similarly in TBI, UL and TBI-UL groups at day 14, suggesting the GH effect on liver IGF-I production was unaffected by skeletal UL. In contrast, GH effect on expression of ALP, IGFBP5 and axin2 in bone were compromised by UL. In conclusion, skeletal UL caused a greater Tb. bone deficit than mild TBI alone and that GH anabolic effects in the TBI and UL groups vary depending on the skeletal site.